The art of imitating life: The potential contribution of biomimicry in shaping the future of our cities. Issue 1 (January 2017) - Taylor Buck, Nick
This paper discusses the significance of biomimicry as a design methodology within the context of urban infrastructure planning and design. The application of biomimicry principles to urban infrastructure problems is examined by analysing case studies that used biomimicry inspired designs rather than 'mainstream' infrastructure approaches. Biomimicry is presented as an ontology of the city that fosters innovative and collaborative urban infrastructure design and management, supplements dominant future city paradigms like the 'smart' city and is worthy of further, detailed study.